Partial purification and characterization of an exonuclease from Xanthomonas oryzae. - Farber, M B (1980)
An exonuclease with a strong preference for single-stranded deoxyribonucleic acid over double-stranded deoxyribonucleic acid has been purified 500-fold from Xanthomonas oryzae. This enzyme liberates 5'-mononucleotides in a reaction which requires Mg2+.